Inovasi dalam Pengembangan Kurikulum: Tantangan dan Peluang di Era Digital - Kartika, Ika; Machmud; Muhammad; Sih Hayuning Tyas Hestutami; M Jahidin (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
In the world of education, what controls all learning orientations for students is the curriculum. The current digital era has a big influence on the state of the curriculum in Indonesia, it is the responsibility of the government and related parties to provide a curriculum that can facilitate the needs of students in facing the era of digitalization, including the challenge of curriculum development in improving digital literacy skills in the midst of technological advances and the current flow of globalization. unavoidable. Curriculum development is essentially a flow of stages starting from making a plan which is carried out by the curriculum developer and then continued by the drafting team, namely the development institution and all activities, which are carried out so that the curriculum developed can be an alternative to solving problems found in educational institutions and can also be catalyst for further national education development.